EFFECT OF VISIBLE RANGE ELECTROMAGNETIC RADIATIONS ON ESCHERICHIA COLI - Azeemi, Samina T. Yousuf; Shaukat, Saleem Farooq; Azeemi, Khawaja Shamsuddin; Khan, Idrees; Mahmood, Khalid; Naz, Farah (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Escherichia coli is the agent responsible for a range of clinical diseases. With emerging antimicrobialresistance, other treatment options including solar/photo-therapy are becoming increasingly common. Visible RangeRadiation Therapy/Colour Therapy is an emerging technique in the field of energy/vibrational medicine that usesvisible spectrum of Electromagnetic Radiations to cure different diseases. In this study, our goal was to understand theeffect of Visible Range Electromagnetic Radiations on E. coli (in vitro) and therefore find out the most appropriatevisible range radiation for the treatment of diseases caused by E. coli.Materials and Methods: A total of 6 non-repetitive E. coli isolates were obtained from urine samples obtained fromhospitalized patients with UTI. Single colony of E. coli was inoculated in 3 ml of Lysogeny Broth (LB) and 40 μl ofthis E. coli suspension was poured into each of the plastic tubes which were then irradiated with six differentwavelengths in the visible region (Table. 1) after 18 hours with one acting as a control. The Optical Densities of theseirradiated samples were then measured. Furthermore, scanning electron microscopy (TEFCAN ZEGA3) was carriedout.Results: The analysis of the microscopic and SEM images of irradiated E. coli samples with six different visible rangeradiations is representative of The fact that E. coli responded differently to every applied radiation in the visible regionand the most profound inhibitory effects were that of 538nm Visible Range Radiation (Green) which proved to bebactericidal and 590nm Visible Range Radiation (yellow) which was bacteriostatic. The enhanced growth of E. coliwith varying degrees was clearly observed in 610nm (orange), 644nm (red), 464nm (Purple) and 453nm (blue).Conclusion: It can be concluded that 538nm (Green) and 590nm (Yellow) can effectively be used for treating E. coliborne diseases.